Crashworthiness analysis of a composite guardrail under impact loading. (July 2023) - Mohammadi, Iman; Haghighi-Yazdi, Mojtaba; Safarabadi, Majid; Yousefi, Armin
Road safety barriers prevent cars from deviating from the roads. Guardrails as common roadside safety barriers protect cars from dangers alongside the roads, such as steep slopes and trees, and redirect traffic from road hazards. Conventional guardrails are generally made of metal or concrete. Although steel guardrails absorb a high amount of crash energy by deformation, these types of guardrails have short lifecycles of less than 15 years. Due to their unique properties, composite materials are potential candidates to use as guardrails. The present study considers the three types of guardrails (steel, composite, and fiber metal laminate (FML)), and the crash model is developed according to standards. LS-DYNA software is employed to simulate and conduct the crash test In the first stage, impact simulation is performed on a carbon/epoxy composite plate. In the next step, impact simulation is performed on a metal fiber multilayer (FML) plate with carbon fiber and aluminum metal. Then, the crash test on the steel guardrail is completely simulated. These three stages are performed to verify the proposed model. In the next stage, the crash test for a carbon/epoxy composite guardrail is simulated, and the effect of different parameters is investigated. Finally, a crash test on the FML guardrail with carbon fibers and steel metal is simulated. Two FML samples with [CE/Steel/CE] layups are considered. The absorbed energy, specific energy, and acceleration severity index (ASI) for all different guardrails are obtained and compared to determine the optimum guardrail regarding energy absorption, mass, and ASI parameters. Results reveal that sample FML-B guardrail is the best of the three guardrail types, with the highest specific energy absorption and lower ASI parameter.